Strategi Peningkatan Mutu Pendidikan Melalui Program Sekolah Peradaban Untuk Mewujudkan Lulusan Yang Berdaya Saing Global - Santi Rahmawati; Hoerudin Hoerudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is motivated by some data and facts. First, there are still many cases of violence that involve or happen to children; second, improving the quality of Human Resources (HR) is one of the important efforts that must be continuously made in improving the quality of education; third, Al Junaediyah IT Vocational School has an interesting program in an effort to improve the quality of education. The research process starts from July 1 – September 20 2022 at SMK IT Al Junaediyah Sukabumi. The research method uses a qualitative method with an analysis process including: data reduction, data display, and data conclusive drawing/verification. The results obtained from this study are: 1) the civilization school program as an integrated program includes improving the quality of human resources, infrastructure, academic and non-academic activities; 2) The strategy for improving the quality of education is carried out through efforts to improve the aspects of: 1) parental participation; 2) class and school management; 3) the professionalism of school principals and teachers; 4) incentives and disincentives; 5) Islamic; 6) knowledge and skills; and 7) discipline. Based on the research results, it can be concluded that the strategy to improve the quality of education through the Civilization School program has been implemented properly and has had a huge impact on graduates. Relevant to these conclusions, the researcher recommends that schools be able to immediately start implementing school management in accordance with international standards.